Sec61p is part of the endoplasmic reticulum-associated degradation machinery - Schäfer, Antje (Nature Publishing Group, 2009)
Endoplasmic reticulum-associated degradation (ERAD) is a cellular pathway for the disposal of misfolded secretory proteins. This process comprises recognition of the misfolded proteins followed by their retro-translocation across the ER membrane into the cytosol in which polyubiquitination and proteasomal degradation occur. A variety of data imply that the protein import channel Sec61p has a function in the ERAD process. Until now, no physical interactions between Sec61p and other essential components of the ERAD pathway could be found. Here, we establish this link by showing that Hrd3p, which is part of the Hrd-Der ubiquitin ligase complex, and other core components of the ERAD machinery physically interact with Sec61p. In addition, we study binding of misfolded CPY(*) proteins to Sec61p during the process of degradation. We show that interaction with Sec61p is maintained until the misfolded proteins are ubiquitinated on the cytosolic side of the ER. Our observations suggest that Sec61p contacts an ERAD ligase complex for further elimination of ER lumenal misfolded proteins.